10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Neural tube defects (NTDs) are congenital anomalies associated with stillbirth, morbidity, disability, and premature death. The absence of population-level data in many settings hinders the planning of effective prevention and intervention strategies. This study aims to determine the prevalence of NTDs in eastern Ethiopia through a population-based surveillance conducted at Hararghe health and demographic surveillance system's (HDSS) sites, eastern Ethiopia, from June 1, 2023, to May 31, 2024. All spontaneous pregnancy losses, children, and adults were eligible for inclusion. A paediatrician confirmed NTD diagnosis and classification. Birth prevalence and the prevalence in the population overall and by sex, age, residence, and NTD types were computed using HDSS and pregnancy surveillance denominators. Overall, 126 NTD cases were enrolled, yielding a birth prevalence of 98.7 (95% CI: 79.8-120.6) per 10,000 births. The prevalence of NTDs in the population was 1.8 (95% CI: 1.4-2.3) per 10,000 population. Prevalence varied by site, being highest in Kersa (birth prevalence: 140.6 (95% CI: 106.4-181.3) per 10,000 births; prevalence in the population: 2.2 (95% CI: 1.5-3.0) per 10,000 population) and in rural areas (birth prevalence: 128.7 (95% CI: 103.9-157.6) per 10,000 births; prevalence in the population: 1.9 (95% CI: 1.4-2.5) per 10,000 population). Spina bifida accounts for 51.6% of cases (birth prevalence: 49.3 (95% CI: 36.3-65.6) per 10,000 births; prevalence in the population: 1.5 (95% CI: 1.1-1.9) per 10,000 population). Of the 126 enrolled, 78 (62%) died during the study period (68 in-utero demises and 10 child deaths). High rates of stillbirths and low survival among affected live births resulted in a low population NTD prevalence contrasting with the high birth prevalence in the study area, particularly in rural areas. Comprehensive preventive strategies, including dietary diversification, preconception counselling, early screening and follow-up, folic acid supplementation, and mandatory folic acid fortification, to reduce NTDs burden, disability, and mortality.